The Mechanism of Forming Hollow Shafts with Constant Wall Thickness by Three-Roll Skew Rolling - Song Zhang; Xuedao Shu; Jitai Wang; Zixuan Li; Haijie Xu; Yingxiang Xia; Zbigniew Pater; Janusz Tomczak; Tomasz Bulzak (Metals, 2024)
To solve the problem of the long forming process for hollow shafts with constant wall thickness (HSCWT), a new process for forming HSCWT, namely three-roll skew rolling, has been proposed. First, the working principle of the three-roll skew rolling process is presented. Then, the finite element model (FEM) of the three-roll skew rolling HSCWT is established. The strain-stress field and temperature field distribution rules of the three-roll skew rolling HSCWT are analyzed with FEM. The stress-strain field of the rolled piece is distributed uniformly along the axial direction but not uniformly along the radial direction. The variation of the temperature field is related to the axial traction velocity. The greater the axial traction velocity, the smaller the variation of the temperature field. The temperature of rolled pieces varies within 100 °C during rolling. Finally, the three-roll skew rolling experiment of the HSCWT is carried out. The results show that the three-roll skew rolling process can form HSCWT. The temperature field of the three-roll skew rolling HSCWT is evenly distributed. The selection of larger axial traction velocity is conducive to the forming of rolled pieces. The three-roll skew rolling technology has achieved near constant temperature forming of HSCWT.